Answer :

Formula :- (I)Let f : AB and g : BC be two functions.


Then, the composition of f and g, denoted by g o f, is defined as the function g o f : AC


given by g o f (x) = g (f (x))


Given:-


(i)f : R R


(ii)g : R R


(iii) f(x) = x2 + x + 1


(iv)g(x) = 1 – x2


Fog(-2)=f(g(-2))


Fog(-2)=f(1-(-2)2)


Fog(-2)=f(-3)


Fog(-2)=(-3)2-3+1=7


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar